AVALIAÇÃO DE BEBIDA LÁCTEA FERMENTADA PROBIÓTICA ADICIONADA DE SOJA E CASTANHA DE BARU - FEGADOLI, Fernanda Pereira; SILVA, Gabrielli Barros; BRITO, Mariana Aparecida; BENEDETTI, Silvia (ANAIS DO ENIC, 2018)
-